Metatranscriptome Library Preparation Influences Analyses of Viral Community Activity During a Brown Tide Bloom - Gann, Eric R.; Kang, Yoonja; Dyhrman, Sonya T.; Gobler, Christopher J.; Wilhelm, Steven W. (Frontiers in Microbiology, 2021)
There is growing interest in the use of metatranscriptomics to study virus community dynamics. We used RNA samples collected from harmful brown tides caused by the eukaryotic alga Aureococcus anophagefferens within New York (USA) estuaries, and in the process observed how preprocessing of libraries by either selection for polyadenylation or reduction in ribosomal RNA (rRNA) influenced virus community analyses. As expected, more reads mapped to the A. anophagefferens genome in polyadenylation-selected libraries compared to the rRNA-reduced libraries, with reads mapped in each sample correlating to one another regardless of preprocessing of libraries. Yet this trend was not seen for reads mapping to the Aureococcus anophagefferens Virus (AaV), where significantly more reads ( two orders of magnitude) were mapped to the AaV genome in the rRNA-reduced libraries. In the rRNA-reduced libraries, there was a strong and significant correlation between reads mappings to AaV and A. anophagefferens. Overall, polyadenylation-selected libraries produced fewer viral contigs, less reads mapped to viral contigs, and different proportions across viral realms and families, compared to their rRNA-reduced pairs. This study provides evidence that libraries generated by rRNA reduction, and not selected for poly-adenylation, are more appropriate for quantitative characterization of viral communities in aquatic ecosystems by metatranscriptomics.